Comparison of early maladaptive schemas between borderline personality disorder and chronic depression. (14th March 2018) - Flink, Niko; Honkalampi, Kirsi; Lehto, Soili M.; Leppänen, Virpi; Viinamäki, Heimo; Lindeman, Sari
Abstract : Borderline personality disorder (BPD) and chronic depression (CD) are common and challenging mental disorders. Maladaptive cognitive schemas have been proposed to increase vulnerability to both disorders. In order to elucidate the role of maladaptive cognitive schemas in BPD and CD, this study compared psychiatric outpatients with BPD ( N = 30) and CD ( N = 30) in terms of early maladaptive schemas (EMSs). The groups were compared using the Young Schema Questionnaire short form‐extended (YSQ‐S2‐extended) and the 15D health status questionnaire. BPD patients showed higher endorsement on the majority of EMSs, poorer social functioning, and greater concurrent distress than CD patients. However, after controlling for concurrent effects of psychological distress, the groups did not differ in 14 out of the 18 EMSs. These findings point to significant similarities in maladaptive beliefs between the 2 disorders and do not support broad, specific patterns of EMSs associated with either disorder. The results highlight the need for further study of the role of maladaptive schemas in the development and treatment of chronic mental disorders.